Effects of chemical modifications of crotoxin B, the phospholipase A2 subunit of crotoxin from Crotalus durissus terrificus snake venom, on its enzymatic and pharmacological activities - Soares, Andreimar Martins (2001)
Crotoxin B, the basic Asp49-PLA2 subunit from crotoxin, the main component of Crotalus durissus terrificus venom, displays myotoxic, edema-inducing, bactericidal (upon Escherichia coli), liposomal-disrupting and anticoagulant activities. Chemical modifications of His (with 4-bromophenacyl bromide, BPB), Tyr (with 2-nitrobenzenesulphonyl fluoride, NBSF), Trp (with o-nitrophenylsulphenyl chloride, NPSC) and Lys (with acetic anhydride) residues of this protein, in addition to cleavage with cyanogen bromide (CNBr) and inhibition with ethylenediaminetetraacetic acid (EDTA), were carried out in order to study their effects on enzymatic and pharmacological activities. Lethality was reduced after modification of His or Lys residues, as well as after cleavage with CNBr, while enzymatic activity was completely abolished after modification of His or incubation with EDTA. Modification of Lys or Tyr, or cleavage with CNBr, partially reduced enzymatic activity. Anticoagulant activity was modified similarly to enzymatic activity, evidencing the dependency of this pharmacological effect on catalytic activity. Myotoxicity was reduced after modification of His or Lys, as well as after cleavage with CNBr, whereas EDTA reduced this effect to a lesser extent. Bactericidal effect was significantly reduced only after modification of Lys and after cleavage with CNBr. Edema-inducing activity was partially inhibited after treatment with EDTA and strongly reduced after acetylation of Lys residues and cleavage with CNBr, being only partially reduced after His alkylation. On the other hand, liposome disrupting activity was only partially reduced after modification of His and Tyr or after cleavage with CNBr. Modification of Trp residue partially reduced lethality and myotoxicity but did not affect enzymatic or anticoagulant activities. These data indicate that enzymatic activity is relevant for some pharmacological effects induced by crotoxin B (mainly lethal, myotoxic and anticoagulant activities), and also evidence that this subunit of crotoxin displays regions different from the active catalytic site which are involved in some of the toxic and pharmacological effects induced by this phospholipase A2.